A Five Element Legacy. - Franglen, Nora (Five Element Acupuncture Ser., 2018)
Nora Franglen reflects on a lifetime of practising five element acupuncture, offering advice and insights into developing patient-practitioner relationships, tailoring treatments to individual patient's needs and the importance of taking your time and trusting your feelings. Invaluable guidance gleaned from a successful career.